Fashion Myths A Cultural Critique (translated by John Irons) - Meinhold, Roman (Kultur- und Medientheorie, 2013)
Besides products and services multinational corporations also sell myths, values and immaterial goods. Such 'meta-goods' (e.g. prestige, beauty, strength) are major selling points in the context of successful marketing and advertising. Fashion adverts draw on deeply rooted human values, ideals and desires such as values and symbols of social recognition, beautification and rejuvenation. Although the reference to such meta-goods is obvious to some consumers, their rootedness in philosophical theories of human nature is less apparent, even for the marketers and advertisers themselves. This book is of special interest for researchers and students in the fields of Cultural Studies, Media Studies, Marketing, Advertising, Fashion, Cultural Critique, Philosophy, Sociology, Anthropology and Psychology, and for anyone interested in the ways in which fashion operates.